German integration model for refugees: processes and perspectives - Polus, Suror Shaba; Mohd Ikbal Mohd Huda, (Penerbit UKM, 2024)
This article examines the German integration model for refugees, focusing on the processes and perspectives that have defined its approach since the 2015 refugee crisis. Germany‘s historical context, robust legal framework, and comprehensive policy measures have shaped its response to the influx of over one million refugees. The objective of this article is to explore the various stages of integration, including language acquisition, education, employment, and social integration, and highlights the socio-political dynamics that influence these processes. Challenges such as bureaucratic hurdles, housing issues, and social integration barriers are discussed, along with case studies from different German cities. Using qualitative methods, this article examines the integration models used in Germany with comparison to other countries. Through a thorough analysis of Germany‘s integration policies, the socio-political environment, and successful local initiatives, this article aims to provide valuable insights for countries facing similar challenges. The research concludes with lessons for other countries and policy recommendations aimed at improving refugee integration efforts. Germany’s model emphasizes a holistic and flexible approach, balancing humanitarian needs with practical integration strategies.